2022
DOI: 10.16910/jemr.15.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements in mild traumatic brain injury: Ocular biomarkers

Abstract: Mild traumatic brain injury (mTBI, or concussion), results from direct and indirect trauma to the head (i.e. a closed injury of transmitted forces), with or without loss of consciousness. The current method of diagnosis is largely based on symptom assessment and clinical history. There is an urgent need to identify an objective biomarker which can not only detect injury, but inform prognosis and recovery. Ocular motor impairment is argued to be ubiquitous across mTBI subtypes and may serve as a valuable clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 174 publications
0
13
0
Order By: Relevance
“…Speci cally, we saw increased functional connectivity from the bilateral cuneus to the cerebellum. We speculate that altered structure of the cuneus and its connectivity with the cerebellum could be associated with abnormal eye movements that often occur following mTBI, such as abnormalities in saccades, smooth pursuit, and vergence [24][25][26]. Unfortunately, we did not measure oculomotor dysfunction in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Speci cally, we saw increased functional connectivity from the bilateral cuneus to the cerebellum. We speculate that altered structure of the cuneus and its connectivity with the cerebellum could be associated with abnormal eye movements that often occur following mTBI, such as abnormalities in saccades, smooth pursuit, and vergence [24][25][26]. Unfortunately, we did not measure oculomotor dysfunction in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that ocular torsion and vertical vergence may be affected independently of one another, where vergence is more readily influenced by optokinetic motion 23 . Unlike vertical vergence, horizontal vergence, allowing for the eyes to converge or diverge to achieve binocular fusion, has been readily studied in the context of concussion and vertigo 35 . Vergence dysfunction in the horizontal axis has been well-documented in concussed patients and is believed to be caused by a general processing delay of afferent signals, causing decreased convergence and divergence velocities due to decreased signal input to key cortical and subcortical structures 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The vestibulo-ocular and vestibulo-spinal tracts are susceptible to the shearing forces in head injury and can be linked to many symptoms and activity limitations in concussion. The most commonly affected visual fixation systems in concussion include smooth pursuit, saccades, near-point convergence, the vestibulo-ocular reflex (VOR), and accommodation (Armstrong 2018 ; Kontos et al 2017 ; McDonald, Holdsworth & Danesh-Meyer 2022 ). Deficits in these systems may create symptoms such as headache, nausea, blurred or double vision, dizziness, difficulty reading or scrolling on a computer, light sensitivity, and eyestrain, all of which impair work or school performance.…”
Section: Our Understanding Of Concussion Todaymentioning
confidence: 99%